Religions of the Silk Road : overland trade and cultural exchange from antiquity to the fifteenth century - Foltz, Richard C (New York St. Martin's Griffin, 1999)
During the latter decades of the nineteenth century, popular European fascination with the world beyond reached an all-time high. The British and French empires spanned the globe, and their colonial agents sent home exotic goods and stories. The Silk Route dates from this romantic period, in name if not in reality. In the century since its invention as a concept, the Silk Route has captured and captivated the Western imagination. It has given us images of fabled cities and exotic peoples. Religions of the Silk Road tells the story of how religions accompanied merchants and their goods along the overland Asian trade routes of pre-modern times. It is a story of continuous movement, encounters, mutual reactions and responses, adaptation and change. Beginning as early as the eighth century BCE, Israelite and Iranian traditions travelled eastwards in this way, and they were followed centuries later by the great missionary traditions of Buddhism, Christianity, Manichaeism, and Islam. The Silk Route was more than just a conduit along which these religions hitched rides East; it was a formative and transformative rite of passage, and no religion emerged unchanged at the end of that arduous journey.
Keywords: Asia--Silk Road; Trade routes; Central Asia